Origins and Originality in Family Therapy and Systemic Practice - Borcsa, Maria; Stratton, Peter (European Family Therapy Association Series, 2016)
The founding volume of the European Family Therapy Association book series presents new ideas confirming the crucial importance of systemic family therapy for family practice. Spanning paradigms, models, concepts, applications, and implications for families as they develop, experts in the field demonstrate the translatability of session insights into real-world contexts, bolstering therapeutic gains outside the treatment setting. Chapters emphasize the potential for systemic family therapy as integrative across theories, healing disciplines, modes of treatment and while contributors' personal perspectives provide unique takes on the therapist's role. Together, these papers promote best practices not only for therapy, but also research and training as professionals delve deeper into understanding the complexity and diversity of families and family systems. Included in the coverage: • The story of an encounter: the systemic approach at the heart of innovative clinical practice. • Steps to an ultramodern family therapy. • From networks to resonance: the life journey of a family therapist. • How to give a voice to children in family therapy. • Systemic theory and narratives of attachment: integration, formulation, and development over time. • Virtual relations and globalized families: the Genogram 4.0 interview. Origins and Originality in Family Therapy and Systemic Practice offers practitioners and other professionals particularly interested in family therapy practice timely, ethical tools for enhancing their work. .